2013
DOI: 10.1088/1748-0221/8/12/p12003
|View full text |Cite
|
Sign up to set email alerts
|

A10B-based neutron detector with stacked MultiWire Proportional Counters and macrostructured cathodes

Abstract: We present the results of the measurements of the detection efficiency for a 4.7Å neutron beam incident upon a detector incorporating a stack of up to five MultiWire Proportional Counters (MWPC) with Boron-coated cathodes. The cathodes were made of Aluminum and had a surface exhibiting millimeter-deep V-shaped grooves of 45 • , upon which the thin Boron film was deposited by DC magnetron sputtering. The incident neutrons interacting with the converter layer deposited on the sidewalls of the grooves have a high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 6 publications
0
25
0
3
Order By: Relevance
“…The recent intense and focused search for alternatives to 3 He-based detectors has shown that detectors based on the boron isotope 10 B are feasible alternatives [1,2] both in their performance and economically [3][4][5][6][7][8][9][10]. 10 B has a relatively high neutron absorption cross section compared to 3 He, and by optimizing the design of the detector, a detection efficiency comparable to 3 He has been presented [3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent intense and focused search for alternatives to 3 He-based detectors has shown that detectors based on the boron isotope 10 B are feasible alternatives [1,2] both in their performance and economically [3][4][5][6][7][8][9][10]. 10 B has a relatively high neutron absorption cross section compared to 3 He, and by optimizing the design of the detector, a detection efficiency comparable to 3 He has been presented [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the radiation hardness has recently been shown to be appropriate for these neutron detector applications [18]. Reference [12] addresses adhesion issues that often arise for micrometer-range-thick B 4 C films due to high residual film stresses in combination with low adhesive forces between the B 4 C film and the substrate. Here, the film adhesion on Al substrates was reported to improve significantly as elevated substrate temperatures between 300 and 400°C are used.…”
Section: Introductionmentioning
confidence: 99%
“…Since the traditional approach with 3 He detectors is no longer a viable option for ESS instruments, owing to the unavailability of 3 He, particularly for the ESS, and its high cost (Persons & Aloise, 2011;Shea & Morgan, 2010;Cho, 2009; International Collaboration on the Development of Neutron Detectors, http://www.icnd.org), an alternative neutron technology solution based on 10 B is introduced for this application. Boron carbide ( 10 B 4 C) thin-film detectors are currently being developed by several groups worldwide and are proven to be a reliable and promising replacement for 3 He detectors (Andersen et al, 2012;Zeitelhack, 2012;Bigault et al, 2012;Correa, 2012;Stefanescu et al, 2013;Hö glund et al, 2012). The 10 B isotope has a neutron absorption cross section of about 3840 barn (1 barn = 10 À28 m 2 ) for thermal neutrons ( = 1.8 Å ) (Safford et al, 1960), which is approximately 70% of the 3 He cross section.…”
Section: The Novel Detector Geometrymentioning
confidence: 99%
“…The largest part of the difference between the detection of an Li ion and an particle is accounted for in the algebraic efficiency calculations, as the two particles have different ranges in the coating layer. For the purposes of this study, the intrinsic detection efficiency of the gaseous detector is reasonably assumed to be very high (Sauli, 1977;Klein, 2000;Stefanescu et al, 2013), with every ion escape leading to a detection event. The conversion layer thickness can be optimized to increase the back-scattering detection efficiency further, as shown in Fig.…”
Section: Evaluation Of the Tube Detector Efficiencymentioning
confidence: 99%
“…This has forced the community to search for alternative solutions 7,8 and the boron isotope 10 B is seen as one of the most promising replacements. [9][10][11][12][13][14][15] The main options are technologies based on 10 B 4 C thin films and this is a field in which the authors' [16][17][18] and Nowak and co-workers' 19 research and development work have enabled rapid progress. These types of detectors are mainly intended for use in large area gaseous neutron detectors and a significant fraction of the detectors at the ESS will be based on this technology.…”
Section: Introductionmentioning
confidence: 99%